The chromosome-scale genome of Kobresia myosuroides sheds light on karyotype evolution and recent diversification of a dominant herb group on the Qinghai-Tibet Plateau. (12th December 2022) - Ning, Yu; Li, Yang; Dong, Shu Bin; Yang, Hong Guo; Li, Chun Yi; Xiong, Biao; Yang, Jun; Hu, Yu Kun; Mu, Xian Yun; Xia, Xiao Fei
Abstract: Kobresia species are common in meadows on the Qinghai–Tibet Plateau. They are important food resources for local livestock, and serve a critical foundation for ecosystem integration. Genetic resources of Kobresia species are scarce. Here, we generated a chromosome-level genome assembly for K. myosuroides (Cyperaceae), using PacBio long-reads, Illumina short-reads, and Hi–C technology. The final assembly had a total size of 399.9 Mb with a contig N50 value of 11.9 Mb. The Hi–C result supported a 29 pseudomolecules model which was in consistent with cytological results. A total of 185.5 Mb (44.89% of the genome) transposable elements were detected, and 26, 748 protein-coding genes were predicted. Comparative analysis revealed that Kobresia plants have experienced recent diversification events during the late Miocene to Pliocene. Karyotypes analysis indicated that the fission and fusion of chromosomes have been a major driver of speciation, which complied with the lack of whole-genome duplication (WGD) in K. myosuroides genome. Generally, this high-quality reference genome provides insights into the evolution of alpine sedges, and may be helpful to endemic forage improvement and alpine ecosystem preservation.